Proceso de atención de enfermería en paciente de 30 años co diagnostico candidiasis vaginal - Acosta Ramos, Alexandra Elizabeth (2018)
Vaginal candidiasis is one of the main reasons for gynecological consultation of women of reproductive age in our country representing between 70 to 90%. The role of the nursing staff is very important in the recovery of patients who are affected by the multiple pathologies that are present in our environment, the general objective of this clinical case was to develop the process of nursing care in a patient of 30 years with diagnosis of Vaginal Candidiasis produced by C. albicans, through the interview and physical examination it was possible to identify the complications and thus be able to contribute with specific care that helped the recovery of the patient's health status. Once developed the nursing interventions are socialized to be applied in the care of the patient, obtaining favorable results and the full recovery of the patient.